Effect of Growing Media Composition and Watering Intervals on the growth of Gmelina arborea Roxb seedlings - Diah Rifdha Fadilah; Zulkaidhah; Rahmawati; Retno Wulandari; Yusran; Gilang Ramahdhan Syahputra (Jurnal Penelitian Pendidikan IPA, 2025)
Gmelina arborea Roxb is one type of forestry plant that has the potential to be cultivated. This is because in addition to having a high economic value, Gmelina arborea Roxb is a plant that is able to grow in critical areas and has a short life cycle. In addition, Gmelina arborea Roxb is one type of wood that has high productivity, high economic value, has a wide natural distribution, has a large genetic variation, can be bred easily, easy to master cultivation techniques, and is resistant to pests and diseases. The purpose of this study was the effect of planting media composition and watering interval on the growth of Gmelina arborea Roxb seedlings. The study used a complete randomised design (RCD) factorial pattern consisting of two factors: The first factor: the composition of planting media, the second factor: watering interval. The results showed that the treatment of media composition and watering intensity treatment and the combination of treatments had a significant effect on the growth of gmelina seedlings. The treatment with the composition of 750 g soil and 250 g cocopeat with watering intensity once a day gave the best results for the growth of gmelina seedlings.